Yield of chicory 'Folha larga' and 'Pão de açúcar' according to planting density - Candian, Joara Secchi; Redigolo, Mateus Vinicius Narciso; Antunes, Walter Luiz de Proença; Cardoso, Antonio Ismael Inácio (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Plant density directly influences the productive potential of crops, and the best density is not the same for all cultivars. Because of a lack of research in this area with chicory, this study aimed to evaluate the effect of plant density on the production of two chicory cultivars, Folha Larga and Pão de Açúcar. Seven planting densities were evaluated (444,444; 370,370; 333,333; 277,778; 266,667; 222,222 and 185,185 plants/ha); the experiment design used a randomized block design with four replications. The fresh weight, plant height, leaf number and yield were evaluated. Despite the fact that density did not influence plant height, mass reduction was observed in the fresh weight and number of leaves per plant and there was an increase in yield of both cultivars with the higher density.